2019
DOI: 10.1016/j.ctro.2018.09.001
|View full text |Cite|
|
Sign up to set email alerts
|

Single dose partial breast irradiation using an MRI linear accelerator in the supine and prone treatment position

Abstract: HighlightsAll MRI-linac plans met the coverage and predefined OAR constraints.The prone approach appeared to be more favorable with respect to the chest wall, and ipsilateral lung dose compared to the supine position.Overall, the MRI-linac and clinical plans were comparable, with minor absolute dosimetric differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(48 citation statements)
references
References 30 publications
(43 reference statements)
3
44
1
Order By: Relevance
“…Because the ERE effect is also present at the lung-tissue interface, it is also important to check the maximum lung and chest wall dose (57,62). Previous planning studies concluded that the effects of the magnetic field on OARs, other than the skin, are generally negligible, and doses were within clinical constraints (60,62,63).…”
Section: Electron Return Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the ERE effect is also present at the lung-tissue interface, it is also important to check the maximum lung and chest wall dose (57,62). Previous planning studies concluded that the effects of the magnetic field on OARs, other than the skin, are generally negligible, and doses were within clinical constraints (60,62,63).…”
Section: Electron Return Effectmentioning
confidence: 99%
“…Because of the design of the hybrid machines, rotations of the table with respect to the gantry angle and therefore irradiation with non-coplanar beams are not possible. No problems are expected because of this because good plan quality for PBI can be achieved with coplanar IMRT (26,63,68). With respect to the methods currently used for dose calculation, co-registration of the planning CT to the pretreatment and/or online MR images or bulk density assignment are currently used for electron density information for both the ViewRay and Elekta hybrid machines (15,67,69).…”
Section: Planning Restrictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly for largebreasted patients, the face-down orientation enables superior lung and chest wall dose sparing. [10][11][12][13][14][15][16][17][18][19][20][21][22][23] Cosmetic outcomes have also been reported to improve with the prone position compared with patients treated supine. 16,24,25 Some investigations have demonstrated reduced skin toxicity, 24,26 whereas others have reported opposite effects.…”
Section: Introductionmentioning
confidence: 99%
“…PBI has been shown to be adequate and may yield better cosmetic results [3] . In contrast to preoperative radiotherapy, when tumor can be visualized and target volumes defined easily [4] , reproducible and standardized techniques to define the cavity and the CTV suitable for PBI are warranted [5] . In the case of target volume definition after lumpectomy, uncertainties may exceed uncertainties from positioning [6] , [7] .…”
Section: Introductionmentioning
confidence: 99%